Purification of NAD-dependent mannitol dehydrogenase from celery suspension cultures. - Stoop, J M (1995)
Mannitol dehydrogenase, a mannitol:mannose 1-oxidoreductase, constitutes the first enzymatic step in the catabolism of mannitol in nonphotosynthetic tissues of celery (Apium graveolens L.). Endogenous regulation on the enzyme activity in response to environmental cues is critical in modulating tissue concentration of mannitol, which, importantly, contribute to stress tolerance of celery. The enzyme was purified to homogeneity from celery suspension cultures grown on D-mannitol as the carbon source. Mannitol dehydrogenase was purified 589-fold to a specific activity of 365 mumol h-1 mg-1 protein with a 37% yield of enzyme activity present in the crude extract. A highly efficient and simple purification protocol was developed involving polyethylene glycol fractionation, diethylaminoethyl-anion-exchange chromatography, and NAD-agarose affinity chromatography using NAD gradient elution. Sodium dodecylsulfate gel electrophoresis of the final preparation revealed a single 40-kD protein. The molecular mass of the native protein was determined to be approximately 43 kD, indicating that the enzyme is a monomer. Polyclonal antibodies raised against the enzyme inhibited enzymatic activity of purified mannitol dehydrogenase. Immunoblots of crude protein extracts from mannitol-grown celery cells and sink tissues of celery, celeriac, and parsley subjected to sodium dodecyl sulfate gel electrophoresis showed a single major immuno-reactive 40-kD protein.